2018
DOI: 10.1016/j.nefro.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia de enfermedad renal crónica en España: impacto de la acumulación de factores de riesgo cardiovascular

Abstract: CKD affects one in seven adults in Spain. The prevalence is higher than previously reported and similar to that in the United States. CKD was particularly prevalent in men, older people and people with cardiovascular disease. Prevalence of CKD increased considerably with the accumulation of CVRF, suggesting that CKD could be considered as a cardiovascular condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(47 citation statements)
references
References 20 publications
2
28
0
10
Order By: Relevance
“…If one takes into account that eGFR declines naturally with age, the increased prevalence of CKD in older age groups might be due not only to real CKD but also to a normal biological variation; our findings related to the prevalence by age are thus consistent with multiple previous results [7,[13][14][15]. The possible overestimation of CKD stages in groups with increased age caused by a CKD misclassification is a matter of concern.…”
Section: Discussionsupporting
confidence: 91%
“…If one takes into account that eGFR declines naturally with age, the increased prevalence of CKD in older age groups might be due not only to real CKD but also to a normal biological variation; our findings related to the prevalence by age are thus consistent with multiple previous results [7,[13][14][15]. The possible overestimation of CKD stages in groups with increased age caused by a CKD misclassification is a matter of concern.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, between 1990 and 2017, the global all-age mortality rate from CKD increased by 41.5% [ 2 ]. In Spain, CKD is present in 15.1% of individuals and this prevalence is more than three times higher in men than in women (23.1% vs. 7.3%) and increases with age [ 3 ]. Diabetes and hypertension are the main causes of CKD in all high-income and middle-income countries and in many low-income countries [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…12 This obesity rate is lower than the one of Gorostidi's study (22.6%) and in Parikh's one (29.3%). 15,20 Jaroszynski's study showed the existence of a relationship between incidence of CKD and obesity (p<0.001). 21 Obesity contributes to serious morbidities and leads to increased disability and mortality.…”
Section: Discussionmentioning
confidence: 99%